Impact of the COVID-19 pandemic on household disinfectant consumption behaviors and related environmental concerns: A questionnaire-based survey in China. Issue 5 (October 2021) - Guo, Jie; Liao, Mengfan; He, Bingshu; Liu, Juan; Hu, Xianmin; Yan, Dan; Wang, Jun
Abstract: Considering the potential hazardous effects of disinfectant residues on environment, organisms and biodiversity, the sharp rise in use of disinfectants during COVID-19 pandemic has been considered highly likely to cause worldwide secondary disasters in ecosystems and human health. This questionnaire-based survey investigated the impact of COVID-19 outbreak on household disinfectant product consumption levels and behavior of 3667 Chinese residents. In particular, in the context that no strategy is currently available to minimize the disinfectant pollution, based on the similarities between disinfectants and pharmaceuticals, we proposed a perspective of ecopharmacovigilance (EPV), which is an effective measure to minimize the environmental risks posed by pharmaceuticals using drug administration protocols, for disinfectant environmental risk management. The public's environmental perceptions, attitudes and the related practices regarding household disinfectant consumption from an EPV perspective were also included in the study. The results showed that the COVID-19 outbreak caused a tremendous rise in the public's household disinfectant consumption and usage levels in China. After the COVID-19 outbreak, the chlorine-based and alcohol-based disinfectants were considered as the most preferred products for household disinfection and hand sanitization, respectively. Importantly, the Chinese public's environmental perceptions and practice on disinfectants were poor. Less than half respondents had positive attitudes toward the source control of disinfectant pollution. The population groups including females, the middle aged adults, those having healthcare professional background, as well as the higher-educated could be focused on to develop targeted efforts for the future control of disinfectant pollution in environment. Graphical Abstract: ga1 Highlights: Huge disinfectant consumption triggered by COVID-19 would cause environmental risks. Ecopharmacovigilance can be adapted and applied to control of disinfectant pollution. A questionnaire-based study involving 3667 Chinese residents. Impact of COVID-19 on household disinfectant product consumption levels and tendency. Environmental perceptions, attitudes and practice regarding disinfectants.